First data on the bionomics of Leptochilus (Euleptochilus) limbiferus (Morawitz, 1867) (Hymenoptera: Vespidae: Eumeninae), with taxonomic notes and new records - Fateryga, Alexander V.; Popovich, Anton V.; Podunay, Yulia A.; Fateryga, Valentina V. (Zootaxa, 2020)
Nesting of Leptochilus limbiferus (Morawitz, 1867) was observed in the Krasnodar Territory, Russia. Twelve nests were studied; all of them were located in empty shells of a terrestrial snail species, Xeropicta derbentina (Krynicki). The building material used by the wasps was pellets of dry soil and gravel particles, as well as shell bits, and sometimes also tiny shells. Females hunted for caterpillars of a gelechiid moth Syncopacma coronillella (Treitschke) and two unidentified species. Imagoes of L. limbiferus were observed feeding on nectar at flowers of five plant species in five families. Males were also observed patrolling the nesting site and sleeping inside a shell of X. derbentina. Nests were invaded by ants and an anthracine fly. Nesting activity and structure of the nests and cocoons are described in detail. The species is univoltine; hibernation occurs at the prepupa stage. The present contribution is the first detailed report on the bionomics of the subgenus Euleptochilus Blüthgen, 1943. Nesting of Old World species of Leptochilus de Saussure, 1853 is discussed with special reference to use of gravel as building material in two phylogenetic lineages: Leptochilus and unrelated genus Alastor Lepeletier de Saint-Fargeau, 1841. The distribution of L. limbiferus is summarized; particularly, the species is reported from Montenegro and Azerbaijan for the first time. At the same time, its previous records from Armenia were found to be based on a misidentification of Leptochilus (Euleptochilus) duplicatus (Klug, 1835) (new for Armenia and the Caucasus as a whole). Leptochilus limbiferus anatolicus Blüthgen, 1955 and L. limbiferus achaeus Gusenleitner, 1970 are treated as synonyms of L. limbiferus s. str. (new synonymies). The lectotype of Odynerus limbiferus Morawitz, 1867 is designated. A key to subgenera of Leptochilus is provided.